Women's Rights to Become Leaders of the Yogyakarta Sultanate Perspective of a Modern Democratic State - Anwar Hidayat (Pustaka Peradaban, 2022)
The right of citizens, including women, to participate in the government of their country is a right guaranteed by the constitution. However, in Law Number 13 of 2012 concerning Privileges of the Special Region of Yogyakarta, this right is limited. Women seem to be hindered in their candidacy for governor and deputy governor of Yogyakarta. In subsequent developments that provision was finally annulled by a decision of the Constitutional Court. This will of course bring certain legal and political implications. Because of this, this article presents the legal aspects surrounding the decision, in particular the background, legal politics, and legal implications of the decision. the study found that the granting of the lawsuit had legal implications of opening up opportunities for women to become governors of DIY. This decision is based on the value of gender equality and the elimination of discrimination against women as well as recognition and respect for the special status of DIY which is also recognized by the constitution. Even though this decision still leaves pros and cons, this decision has been in line with democratic values and reflects the paradigm of gender equality and support for the gender mainstreaming movement in Indonesian politics.